Motivations to Adopt Plant-Based Diets: Data from the Adhering to Dietary Approaches for Personal Taste (ADAPT) Study (P16-024-19). (13th June 2019) - Miki, Akari; Karlsen, Micaela; Livingston, Kara; Rogers, Gail; Folta, Sara; Lichtenstein, Alice; Jacques, Paul; McKeown, Nicola
Abstract: Objectives: To examine the differences in key motivations to adopt a dietary pattern (1) between self-reported plant-based diet followers and omnivores, and (2) among three types of plant-based diet followers: whole food, plant-based (WFPB), vegan, and vegetarian+pescatarian. Methods: Adhering to Dietary Approaches for Personal Taste (ADAPT) is an online survey that recruits followers of popular diets. Of the 2010 enrolled participants, 1227 participants described their diet as plant-based, either WFPB ( n = 705), vegan ( n = 388), vegetarian ( n = 103), or pescatarian ( n = 31). The remaining 783 participants were categorized as omnivores. A multiple choice question with a free text option prompted participants to indicate their reasons for adhering to their self-identified dietary pattern, and a follow-up question asked them to rank their key motivations for adherence. The percentage of participants who chose each response as one of their top 2 key motivators was tabulated within each dietary pattern. Logistic regression, adjusted for age and gender, was used to compare the prevalence of top reasons among dietary patterns. The results were considered significant if < P = 0.05 after Bonferroni correction. Results: The majority of both plant-based diet followers (79%) and of omnivores (83%) identified disease prevention and overall wellness as top motivations for following their dietary patterns. Significantly more plant-based diet followers, versus omnivores, chose helping the environment (17% vs. 4%) and supporting animal welfare (28% vs. 1%). Significantly more omnivores chose enjoyment (39% vs. 26%) and the need to address a specific health concern (44% vs. 29%). Significantly more WFPB followers (87%) chose disease prevention and overall wellness compared to vegans (71%) and vegetarians+pescatarians (66%). Significantly more vegans (47%) and vegetarians+pescatarians (33%) chose animal welfare than WFPB followers (15%). Conclusions: The dietary motivations of plant-based diet followers are more diverse compared to those of omnivores. Among plant-based diet followers, WFPB followers often chose health motivations, and vegans, vegetarians, and pescatarians often chose ethical motivations. Funding Sources: The Lisa Wendel Memorial Foundation, Tufts Collaborates Seed Grant, Tufts Summer Scholars Grant, and USDA ARS agreement No. 58-1950-4-003.